Escape from reality in the modern Arabic novel The self-style is representative (Journal of the College of Basic Education, 2023)
This research deals with an artistic-psychological phenomenon in the modern Arabic novel, which is the phenomenon of escaping.of fact. The researcher tried to extend the concept of escaping from reality in the introduction, and referred it to threepatterns are:1. Psychological type.2. The mythological pattern.3. Religious style.And shed light, in the body of the research, on the psychological style and its embodiments in the Arabic novel.Modern: dreams, daydreams and delirium. Where the researcher finds that the prevalence of this pattern inThe Arab novelist art came because of the crisis of the modern Arab man in light of the political changes.the economic and social aspects of the twentieth century.It is worth noting that the researcher was keen to select indicative Arabic novel models, and did not meanBy extrapolating the history of the phenomenon under study.The researcher reached the following results:1. The prevalence of the phenomenon of escaping from reality in its psychological style in the modern Arabic novel.2. The conscious artistic employment of psychological activities that embody psychological escape in the novel.Modern Arabic.3. The phenomenon of escaping from reality embodies the theme (subject) of the novel as a whole.4. The contribution of the phenomenon of escaping from reality in the development of the artistic side of the modern Arabic novel..